Come back, Amelia Bedelia - Parish, Peggy; Tripp, Wallace (New York : Harper & Row., 1971)
Because she does exactly as she is told, Amelia Bedelia is fired from one job after another.
G1
Keywords: Work -- Fiction; Humorous stories